Portrait of the St. Claire Club - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of members belonging to the St. Claire Club. The Oaks and foliage in the background are very similar to images of the Bull's Head Breakfast, a club tradition.